Firm Level Decisions and Human Resource Development in an Islamic Economy (American Journal of Islam and Society, 1993)
Japan and Germany were totally destroyed during the Second WorldWar. Their industrial complexes lay in ruins after the devastating Alliedair bombardments. Both countries emerged from the war under Allied occupationand with almost all of their manufacturing facilities and infrastructures,such as transportation and telecommunications, paralyzed. Apicture of war-ravaged Japan appeared in the Nippon Times of 23September 1946:In Tokyo, 70 percent of the area of the city was destroyed, inOsaka 80, in Nagoya 90. Transportation was limited to crowded,creaky trains, hand-pulled two-wheel 'rear cam' designed to beattached to bicycles and ox carts. At war's end, in all of Japanthere were only 41,000 motor vehicles, half of them inoperableand almost all the rest powered by charcoal fumes. There wereno street lights at night and very few house lights.Germany's infrastructure suffered a similar fate:The condition of Germany at the end of World War II was desperate.The country seemed to be one vast rubble dump. Theeconomy was in ruins; factories, railroads, ports, and canals hadbeen destroyed; and many millions had-lost their homes. Many ...